Analytical Method of Temperature Prediction in Reinforced Concrete Beams. (1st December 2014) - Rafi, Muhammad; Nadjai, Ali
Abstract : The determination of temperature profile within a reinforced concrete (RC) beam is essential for carrying out structural analysis at elevated temperatures. The temperatures are usually estimated using sophisticated numerical techniques which require computational support. Since the determination of rebar temperature in RC beams is more important than the concrete temperature a reliable analytical method of temperature prediction can become a helpful tool in simple beam analysis problems which are employed for determining residual strength in fire. This paper presents the details of development of an empirical equation for the prediction of temperature of rebar in RC beams. The equation is also capable of predicting concrete temperatures at different locations within the beam. The predictions made by the equation were compared with the temperatures determined from experimental beam testing and finite element (FE) analysis. A good correlation of the predicted temperatures was found for the entire time-temperature history with both the observed data and the estimated temperatures by FE models.